Strengthening critical thinking through joyful learning implementation using the semantic wave approach - Eka Fitrajaya Rahman; Jajang Kusnendar; Renisa Nur Kamelia Putri; Sarah Nurhaliza (Inovasi Kurikulum, 2025)
Along with the rapid advancement of technology, critical thinking skills have become essential competencies for students. However, in education, many learning methods remain conventional and do not yet optimally support the development of students' critical thinking skills. Implementing joyful learning in combination with the semantic wave approach, it is expected that students will gain a learning experience that is more enjoyable, meaningful, and systematically structured. The purpose of this study is to analyze the effectiveness of applying joyful learning with the semantic wave approach in enhancing students’ critical thinking abilities. This research utilizes the Classroom Action Research (CAR) method, consisting of three cycles designed to evaluate the implementation of joyful learning based on the semantic wave approach. The results indicate a significant increase in pretest and posttest scores, with an average improvement, accompanied by a reduction in students’ learning achievement gaps. Furthermore, findings from the pre-cycle stage revealed low levels of motivation, engagement, and analytical skills among students in understanding the material. Through the implementation of the joyful learning model based on the semantic wave approach, there was a proven increase in students’ active participation, gradual conceptual understanding, and overall learning outcomes.   Abstrak Seiring dengan pesatnya kemajuan teknologi, keterampilan berpikir kritis menjadi salah satu kompetensi penting yang perlu dimiliki oleh peserta didik. Meskipun demikian, realitas di dunia pendidikan menunjukan bahwa metode pembelajaran masih banyak yang bersifat konvensional dan belum optimal dalam mendukung pengembangan keterampilan berpikir kritis murid. Penerapan joyful learning yang dipadukan dengan pendekatan semantic wave, diharapkan dapat menyebabkan murid memperoleh pengalaman belajar yang lebih menyenangkan, bermakna, dan terstruktur secara sistematis. Tujuan penelitian ini untuk menganalisis efektivitas penerapan joyful learning dengan pendekatan semantic wave dalam meningkatkan kemampuan berpikir kritis murid. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang terdiri dari tiga siklus, yang dirancang untuk mengevaluasi implementasi joyful learning berbasis semantic wave. Hasil penelitian ini menunjukan nilai pretest dan posttest meningkat signifikan, dengan rata-rata nilai meningkat, disertai kesenjangan hasil belajar murid semakin kecil. Selain itu, temuan pada tahap pre-cycle menunjukkan rendahnya motivasi, keterlibatan, dan kemampuan analisis murid dalam memahami materi. Melalui implementasi model joyful learning berbasis semantic wave yang dilakukan, terbukti terjadi peningkatan partisipasi aktif murid, pemahaman konsep secara bertahap, serta hasil evaluasi belajar. Kata Kunci: berpikir kritis; joyful learning; pembelajaran abad ke-21; semantic waves